An Ultra‐Low‐Temperature Elastomer with Excellent Mechanical Performance and Solvent Resistance. Issue 36 (24th July 2021) - Ma, Qiang; Liao, Shenglong; Ma, Yingchao; Chu, Yanji; Wang, Yapei
Abstract: Elastomers presenting good elasticity, ductility, and chemical resistance at low temperatures can serve as superior performers for explorations in extremely cold environments. However, no commercially available elastomer to date can comprehensively fulfill those demands. Here, a perfluoropolyether (PFPE)‐based network crosslinked by dynamic urethane chemistry is demonstrated, which may satisfy the demands of application in ultracold environments. As the crucial constitute in such a crosslinked network, PFPE provides the elastomer with excellent elasticity at a temperature down to −110 °C and outstanding ductility within the cryogenic temperature range. Importantly, the high proportion of fluorocarbon segment also provides wonderful compatibility to most organic solvents, accounting for the low‐swelling characteristics of the elastomer in sealing applications. Furthermore, the dynamic crosslinking feature allows the cured elastomer to be reprocessed like thermoplastic polymers, which affords great promise to recycle and reuse the elastomer after its disposal. Inherently, this elastomer would inspire a worldwide interest in the design of elastic devices that are adaptable to extremely low temperature. Abstract : A series of perfluoropolyether (PFPE)‐based elastomers crosslinked by dynamic urethane are reported, which exhibit excellent elasticity at temperature down to −110 °C and outstanding ductility within the cryogenic temperature range. Moreover, the high proportion of fluorocarbon segments also provides wonderful compatibility to most organic solvents, accounting for the low‐swelling characteristics of the elastomer in low‐temperature sealing applications.